Moment‐Volume Coupling in La(Fe1−xSix)13. Issue 2 (18th December 2017) - Gruner, Markus E.; Keune, Werner; Landers, Joachim; Salamon, Soma; Krautz, Maria; Zhao, Jiyong; Hu, Michael Y.; Toellner, Thomas; Alp, Esen E.; Gutfleisch, Oliver; Wende, Heiko
Abstract : We investigate the origin of the volume change and magnetoelastic interaction observed at the magnetic first‐order transition in the magnetocaloric system La(Fe1− x Si x )13 by means of first‐principles calculations combined with the fixed‐spin moment approach. We find that the volume of the system varies with the square of the average local Fe moment, which is significantly smaller in the spin disordered configurations compared to the ferromagnetic ground state. The vibrational density of states obtained for a hypothetical ferromagnetic state with artificially reduced spin‐moments compared to a nuclear inelastic X‐ray scattering measurement directly above the phase transition reveals that the anomalous softening at the transition essentially depends on the same moment‐volume coupling mechanism. In the same spirit, the dependence of the average local Fe moment on the Si content can account for the occurence of first‐ and second‐order transitions in the system. Abstract : La(Fe1− x Si x )13 is a promising magnetocaloric system with a first‐order transition showing a large volume change and strong magnetoelastic interactions. First‐principles calculations reveal a close correspondence between spin disorder, average magnetic moments and atomic volume. The comparison with nuclear inelastic X‐ray scattering experiments reveals that lattice softening and volume change at the transition primarily derive from the interplay between electronic density of states, magnetic moments and atomic volume, rather than magnetic disorder. In the same spirit, the dependence of the average local Fe moment on the Si content can account for the occurrence of first‐ and second‐order transitions in the system.